Optimal storage model to sustain the operation of Baghdad stations Establish an - Ali Mohammed, Ahmed; Mahdi Alwan, Faris ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
The research presented the improvement of the performance of the continuous review inventory and finding the best policy for inventory management by finding the optimal economic quantity and reorder point and to prevent the depletion of inventory (deficit) and reduce additional costs with little time and effort. The sample of this research is the chemical storage data of the South Baghdad thermal power plant affiliated to the Ministry of Electricity the Middle Production Company for the period from 2019 to 2023 The demand data was divided into two period (winter –summer ). the statistical analysis of the demand data was conduction using the statistical program (easy fit 5.6) which concluded that the demand data from the inventory models are of the deterministic type (deterministic Inventory model) on this basis the mathematic model was created and the solution steps were applied using the traditional method of solving equations and through the (win Qsb) program, as well as programming the solution was the (R- programming) program. the result showed that all solutions matched the current model and the proposed model, as the inventory size and costs inventory in the water treatment process were reduced based on the results of the difference between the two models purchase costs and finding re-order point and safety stock.